Celebrating Europe : An Asian Journey - Asad Latif (Book collections on Project MUSE., 2012)
Europe's mythical origins lie in Zeus' abduction of the Asian princess Europa. Down the real centuries, Asia has played a crucial role in the making of Europe - as an object of Orientalist fantasy and colonial desire, but also of the spread of the liberating values and humane letters associated with the continent. In this book, a lifelong admirer of Europe casts a critical yet loving eye on the continent to ask what it means to him. The book revolves around a series of personal encounters. These range from following his father to Cambridge, and meeting two Bengali lovers in Calcutta who cheris.